Grammatik i bilingvale ordbøger - Bergenholtz, Henning (LexicoNordica, 1995)
In the greater part of the many contributions conceming grammar in dictionaries that have appeared during the past 15 years, the tnain focus has been on monolingual dictionaries. Major parts of this discussion are very relevant to bilingual lexicography. In a bilingual context, however, a number of problems deserve special attention: (a) The need for grammatical information in a bidirectional dictionary by both Ll and L2 users. (b) The distribution of grammatical information across dictionary articles as well as dictionary outside matter. (c) The design of a dictionary grammar for Ll and/or L2 in a bidirectional dictionary.